Spatial-temporal characteristics of carbon emissions from land use change in Yellow River Delta region, China. (March 2022) - Zhang, Chun-yan; Zhao, Lin; Zhang, Haotian; Chen, Meng-na; Fang, Ru-yao; Yao, Ying; Zhang, Qi-peng; Wang, Qian
Highlights: The spatial-temporal characteristics of carbon emissions are different for each land use type. Construction land is the main source of carbon. Carbon emissions in the Yellow River Delta were spatially clustered. The distribution of carbon emissions is larger in the "east-west" than in the "north-south". Abstract: Land use is a major source of anthropogenic carbon emissions and a driver of climate change, so it is necessary to explore the spatial and temporal distribution characteristics of carbon emissions from different land use types. Based on the land use type data and fossil energy consumption data in the same period, we analyzed the spatial and temporal distribution characteristics of carbon emissions in the Yellow River Delta from 2000 to 2019 by constructing a carbon emission model, carbon footprint and Moran's I index. The empirical results show that total net carbon emissions in the Yellow River Delta increased from 3.1×10 10 kg to 1.5×10 11 kg during 2000–2019. Construction land is the main source of carbon, while forest land and water contribute more to the total carbon sink in the study area. Carbon emissions in the Yellow River Delta were spatially clustered, characterized by a larger distribution of carbon emissions in the "east-west" direction than in the "north-south" direction. The results of the study are conducive to a comprehensive understanding of the spatial distribution pattern of land use carbon sources/sinks in the Yellow River Delta, and provide a certain reference basis for the formulation of low-carbon economic policies in the region.